Liquid crystals for IR: Part II synthesis and properties of perfluoroalkyl- or perfluoroalkoxy-terminated tolanes. Issue 14 (7th December 2020) - Harmata, Piotr; Herman, Jakub; Kula, Przemysław
ABSTRACT: This article is a continuation of previously published 'Liquid crystals for IR: Part I' article. Several homologous series of laterally halogenated and perfluoroalkyl- or perfluoroalkoxy-terminated tolanes derivatives have been synthesised. Obtained compounds were divided into three families, i.e. tolanes, phenyltolanes, bistolanes and their mesomorphic properties, phase transition temperatures and enthalpies were determined. The influence of the length of the core, type and position of substituents in the molecular core has been analysed. The lack of aliphatic protons in molecular structure generates unique infrared properties of presented materials and their mixtures. Graphical Abstract: uf0001